Biochemical properties and antimicrobial and antioxidant activity of blackberry growing naturally in Kelkit valley - Aglar, Erdal; Sumbul, Ahmet; Karakaya, Orhan; Erturk, Omer; Ozturk, Burhan (Journal of Postharvest Technology, 2021)
The study was carried to determine the pomological, biochemical and antimicrobial properties of wild blackberry fruit, which we think that is different with its taste and fruit size in the Kelkit valley where is a very rich region in terms of biology diversity due to its different and favorable ecological conditions. At the harvest, 5 kg fruit was collected. Fruit was immediately transported at 10±1.0 °C and 80±5.0 for 2 h by frigorific vehicles to postharvest physiology laboratory of Horticulture Department of Ordu University. Pomological, biochemical and antimicrobial measurements and analyses were made on fruits. Fruit width, length, height and weight were 15.84 mm, 15.37 mm, 15.72 mm and 2.16 g respectively. In the study, the soluble solids content (SSC) ratio, titratable acidity and vitamin C concentration of the genotype was determined as 9.2%, 1.34% and 20.1 mg 100 g−1 FW respectively. Total phenolic content was 2158 mg GAE kg −1 FW, total flavonoid was 544 mg QE kg −1 FW, DPPH and FRAP (antioxidant activity) values were 2749 µmol TE kg −1 and 6379 µmol TE kg −1 respectively. The solution obtained in blackberry in the study had an antimicrobial effect on all bacteria and fungi. The highest antimicrobial activity against bacteria was obtained against Escherichia coli, while the lowest effect was against Klebsiella pneumonial bacteria. In fungi, it was determined that the effect on Candida albicans was higher. The study is very important in terms of being a source for future breeding studies in this sense.